2017
DOI: 10.1111/gwao.12176
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change

Abstract: The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments' policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in‐depth interviews with women working in the Netherlands' creative industries. Data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 92 publications
(130 reference statements)
1
51
0
12
Order By: Relevance
“…structural characteristics of organizations that are expected to produce increased job satisfaction and engagement also reduce the incidence of sexual harassment (Ollo-López and Nuñez 2018; Timmerman and Bajema 2000), . the type of contract that employees work under is related to their risk of being subjected to sexual harassment, where more secure jobs result in a reduced risk of victimization (Hennekam and Bennett 2017;Mueller, De Coster, and Estes 2001), . well-integrated, structurally egalitarian workplaces where women and men share power and leadership equally prevents sexual harassment; women in male-dominated workplaces are at greater risk of sexual harassment (Cogin and Fish 2007;also cf.…”
Section: Other Organizational Factorsmentioning
confidence: 99%
“…structural characteristics of organizations that are expected to produce increased job satisfaction and engagement also reduce the incidence of sexual harassment (Ollo-López and Nuñez 2018; Timmerman and Bajema 2000), . the type of contract that employees work under is related to their risk of being subjected to sexual harassment, where more secure jobs result in a reduced risk of victimization (Hennekam and Bennett 2017;Mueller, De Coster, and Estes 2001), . well-integrated, structurally egalitarian workplaces where women and men share power and leadership equally prevents sexual harassment; women in male-dominated workplaces are at greater risk of sexual harassment (Cogin and Fish 2007;also cf.…”
Section: Other Organizational Factorsmentioning
confidence: 99%
“…The use of sexual harassment and sexual violence is considered a legitimate and expected means for men to express their masculinity and reinforce their positions of power (Robinson). Women in creative industries in The Netherlands reported sexual harassment as a prevalent and normalized part of occupational culture and a necessary part of career establishment or enhancement (Hennekam and Bennett). Women in supervisory positions are more likely to experience sexual harassment, in part as a tool to enforce gender appropriate behavior and accept it in order to keep their jobs (McLaughlin et al.).…”
Section: Sexual Harassment Sexual Assault Hegemony and The Mediamentioning
confidence: 99%
“…These findings are not conclusive, however, and are compounded by research noting that women in male-dominated professions do not always perceive or define workplace actions as sexual harassment [33,34] A final theme within the literature on workplace climate addresses co-worker competition [35,36] In some workplaces like music and other creative industries, competition for work is routine because of the itinerant nature of employment, which puts power in the hands of those with authority to hire workers. Hennekam and Bennett [37] found that sexual harassment is not only tolerated, but that competition for work re-inscribed the normalization of sexual harassment in job interviews and auditions. This prevailing sense of competition creates further stressors on individuals, since they must generate networking outside of work; and their chances of further being victimized can increase [38,39].…”
Section: Literature Reviewmentioning
confidence: 99%